PH and glucose responsive nanofibers for the reversible capture and release of lectins. (17th September 2014) - Wang, Yinan; Kotsuchibashi, Yohei; Uto, Koichiro; Ebara, Mitsuhiro; Aoyagi, Takao; Liu, Yang; Narain, Ravin
Abstract : A dual pH and glucose responsive boronic acid containing nanofiber was constructed for the reversible capture and release of lectins. Abstract : A dual pH and glucose responsive boronic acid containing nanofiber was constructed for the reversible capture and release of lectins. The effects of surface groups and pH values on selective lectin capture were investigated by fluorescence microscopy. Compared to the pristine nanofibrous membrane, glucose and galactose functionalized nanofiber surfaces showed significantly higher capture of ConA and Jacalin, under alkaline conditions. On the other hand, treatment of the modified nanofibers with an acidic solution resulted in the detachment of both the lectins and glycopolymers from the nanofiber surface. As expected, once the glycopolymers are displaced, no lectins were adhered to the nanofiber surface under alkaline conditions. These functional nanofibers can therefore be easily modified and hence can be used for quick removal of selective proteins or toxins from the solution.